2003
DOI: 10.1051/forest:2003044
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and growth in newly established plantations of Eucalyptus globulus in northwestern Spain

Abstract: -The growth and nutritional status of newly established Eucalyptus globulus plantations, located in NW Spain, were studied in relation to soil properties and site preparation techniques. Most of the plantations are growing on chemically poorly fertile soils of intermediate depth. Despite being fertilized at establishment, most of the plantations showed low foliar levels of P and Ca, and some showed deficiencies of Mg and K. Growth depended mainly on the altitude, length of the drought period and on concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 27 publications
1
37
0
7
Order By: Relevance
“…Both natural forests and mixed stands had better hydrological function than monospecific tree plantations (Liu et al 2003). Large amounts of nutrients were lost from fast-growing monoculture plantations through timber harvesting (Merino et al 2003(Merino et al , 2005. Proença et al (2010) reported that 28 plant species were observed in eucalypt plantation, while 52 and 33 were observed in oak forest and pine plantation, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Both natural forests and mixed stands had better hydrological function than monospecific tree plantations (Liu et al 2003). Large amounts of nutrients were lost from fast-growing monoculture plantations through timber harvesting (Merino et al 2003(Merino et al , 2005. Proença et al (2010) reported that 28 plant species were observed in eucalypt plantation, while 52 and 33 were observed in oak forest and pine plantation, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In additional studies carried out in commercial plantations, observed volume growth increases always higher than 38% relative to the unfertilized control two years after planting. The recommended doses at planting are summarized in Table 1, which also includes results reported by Merino et al [35] and Vega-Nieva et al [44] and the risk of fertilizer leaching in the rainier regions. Unsurprisingly, responses to mainly N and P were found in the soil with low organic matter content in SW Spain (Mediterranean climate, with rainfall between 450 and 950 mm year´1) [43].…”
Section: Planting Fertilizationmentioning
confidence: 99%
“…The average nutrient concentrations in leaves of some Eucalyptus globulus plantations in Spain are shown in Table 2. Merino et al [35] found that foliar concentrations of N and micronutrients were satisfactory in all of the 44 E. globulus plantations aged 2-6 years assessed in northwest Spain. However, levels of P and Ca were low in most of the plantations, and levels of Mg and K were low in some plantations.…”
Section: Assessing the Nutritional Status And Completing A Nutrient Bmentioning
confidence: 99%
See 1 more Smart Citation
“…In Spain, tree biomass equations for this species have been fitted in Galicia (Balboa-Murias et al, 2006), along with general models for the country as a whole (Montero et al, 2005). In addition, other studies have been conducted that relate biomass production of radiata pine with soil properties or nutrient accumulation (Rey et al, 2001;Merino et al, 2003). Recently, BalboaMurias et al (2006) carried out a study of the temporal variations and distribution of carbon storage in radiata pine and maritime pine pure stands under different silvicultural management.…”
Section: Introductionmentioning
confidence: 99%